Massive hydatid cysts in the lung and liver of a 4‐year‐old boy - Yu, Uet (Clin Case Rep, 2020)
Hydatids may persist for years if left undiagnosed. Early identification is challenging, especially in patients from nonendemic regions. It is crucial for clinicians to be aware of the presence of the disease to avoid devastating outcomes.